2005
DOI: 10.1111/j.1399-6576.2005.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceleromyography vs. electromyography: an ipsilateral comparison of the indirectly evoked neuromuscular response to train‐of‐four stimulation

Abstract: Acceleromyographic TOF values tend to overestimate the extent of EMG recovery. Acceleromyographic TOF values <0.90 are indicative of incomplete neuromuscular recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 18 publications
7
67
2
1
Order By: Relevance
“…ONSET T1 5%, the first train-of-four (TOF) response (T1) diminished by 95%; OFFSET T1 25%, the recovery of T1 to 25% of the initial calibration; OFFSET TOF 0.9, recovery of T4/T1 ratio of 0.90. studies have shown that applying a slight elastic preload to the thumb can reduce the extent of the 'reverse fade'. 8,9 A recent study investigating the role of the 'elastic recoil' obtained with the Hand Adapter has shown that such a device can improve the precision of AMG. Unfortunately, the average control TOF ratios increased from 1.07 (no preload) to 1.13 (range between 1.01 and 1.23) with the Hand Adapter, thereby increasing the bias in relation to MMG.…”
Section: Initial Baseline Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…ONSET T1 5%, the first train-of-four (TOF) response (T1) diminished by 95%; OFFSET T1 25%, the recovery of T1 to 25% of the initial calibration; OFFSET TOF 0.9, recovery of T4/T1 ratio of 0.90. studies have shown that applying a slight elastic preload to the thumb can reduce the extent of the 'reverse fade'. 8,9 A recent study investigating the role of the 'elastic recoil' obtained with the Hand Adapter has shown that such a device can improve the precision of AMG. Unfortunately, the average control TOF ratios increased from 1.07 (no preload) to 1.13 (range between 1.01 and 1.23) with the Hand Adapter, thereby increasing the bias in relation to MMG.…”
Section: Initial Baseline Valuesmentioning
confidence: 99%
“…The TOF-Guard/TOFWatch arm board (Organon, Oss, The Netherlands) fixes and protects the hand from external disturbances and it is suggested that it is used with an elastic band to provide a modest preload to the thumb (<150 g). 8,9 Despite the increased measurement stability provided by this device, it is too cumbersome to be adapted to most clinical requirements. The Hand Adapter (Organon), a small thumb preload device, ensures that the thumb does not touch the palm during adductor pollicis contractions.…”
Section: Introductionmentioning
confidence: 99%
“…19 The ba se li ne AMG-TOF ra ti os va ri ed wi dely [110.8 (91-149)] in the cur rent study, si mi lar to pre vi o us stu di es. 11,16,17,20 Even tho ugh the ba se li ne TOF ra ti os we re >1 in 71 (58.1%) pa ti ents, they were <1 in 29 (23.7%) pa ti ents. Thus, if PORC had been con si de red as a raw TOF ra ti o less than 1 in this study, five pa ti ents wo uld ha ve be en er ro ne o usly ac cep ted as ha ving PORC (po si ti ve pre dic ti ve valu e; 92%).…”
Section: Discussionmentioning
confidence: 94%
“…Accuracy is dependent on the mass of the acceleromyographic probe. In a recent study, Kopman et al 43 showed that the addition of an elastic preload to the thumb decreased the TOF variability without any effect on the relationship between twitch height and the TOFratio. At present, AMG is the most accurate and reliable monitoring method commercially available to measure NMB objectively in routine clinical settings.…”
Section: Acceleromyographymentioning
confidence: 98%